Addressing the structural sophistication of meat via plant-based tissue engineering - Dikovsky, Daniel (Frontiers in Soft Matter, 2024)
The escalating environmental impact of traditional livestock farming, particularly beef production, has spurred the search for sustainable meat alternatives. This study introduces a novel Plant-Based Tissue Engineering (PBTE) approach, to replicate the complex structure and sensory experience of whole-muscle cuts of meat using plant-based ingredients. Leveraging principles of tissue engineering and advanced food manufacturing technologies, PBTE deconstructs meat into its fundamental components: muscle, fat, and connective tissue, and reconstructs them using a combination of plant proteins, fats and polysaccharide materials. The muscle component is reassembled to mimic the anisotropic fibrous structure of beef, while the fat component is engineered through lipid encapsulation within a hydrocolloid matrix. Advanced manufacturing techniques, including additive manufacturing and robotics, are utilized for precise spatial configuration and assembly of these components. Our findings demonstrate that PBTE can effectively replicate the mechanical integrity, texture, and sensory attributes of traditional meat, presenting a promising alternative that could significantly reduce the environmental footprint of meat production. This approach aligns with the principles of Soft Matter in the manipulation of artificial structures and materials for mimicking naturally occurring designs, such as whole cut meat foods. It also holds substantial potential for revolutionizing the alternative protein industry by catering to a broader consumer base, including flexitarians and meat-eaters.